Treatment of primary Sjögren's syndrome with ianalumab (VAY736) targeting B cells by BAFF receptor blockade coupled with enhanced, antibody-dependent cellular cytotoxicity. Issue 5 (2nd March 2019) - Dörner, Thomas; Posch, Maximilian Georg; Li, Yue; Petricoul, Olivier; Cabanski, Maciej; Milojevic, Julie Marie; Kamphausen, Esther; Valentin, Marie-Anne; Simonett, Claudia; Mooney, Louise; Hüser, Andreas; Gram, Hermann; et al.
Abstract : Objectives: To evaluate the efficacy and safety of ianalumab (VAY736), a B cell-depleting, B cell activating factor receptor-blocking, monoclonal antibody, in patients with active primary Sjögren's syndrome (pSS) in a double-blind, placebo-controlled, phase II, single-centre study. Methods: Patients with pSS, EULAR Sjögren's Syndrome Disease Activity Index (ESSDAI) ≥6, were randomised to ianalumab single infusion at either 3 mg/kg (n=6), 10 mg/kg (n=12) or placebo (n=9). Outcomes were measured blinded at baseline and weeks 6, 12, 24, and unblinded at end of study (EoS) when B cell numbers had recovered. Clinical outcomes included ESSDAI, EULAR Sjögren's Syndrome Patient Reported Index (ESSPRI), salivary flow rate, ocular staining score, physician global assessment and patient assessments of fatigue and general quality of life. Laboratory-based measures included circulating leucocyte subsets and markers of B cell activity. Results: A similar trend showing positive therapeutic effect by ianalumab was observed across the primary clinical outcome (ESSDAI) and all secondary clinical outcomes (ESSPRI, Multidimensional Fatigue Inventory, Short Form-36, global assessments by physician and patient) versus the placebo-treated group. Rapid and profound B cell depletion of long-lasting duration occurred after a single infusion of ianalumab at either dose. Serum Ig light chains decreased, with return to baseline levels at EoS. Changes in some clinical outcomes persisted through to EoS in the higher dose group. Adverse effects were largely limited to mild to moderate infusion reactions within 24 hours of ianalumab administration. Conclusions: Overall results in this single-dose study suggest potent and sustained B cell depletion by ianalumab could provide therapeutic benefits in patients with pSS without major side effects.